THE INFORMATION NEEDS AND SEEKING BEHAVIOUR OF THE IMR BIOMEDICAL SCIENTISTS - Zawawi, Salina; Majid, Shaheen (Malaysian Journal of Library and Information Science, 2001)
Little attention has been focused on the information needs and informationseeking behavior of health science professionals in developing countries, particularly in Malaysia. This study explores the information needs and seeking behavior of biomedical scientists at the Institute for Medical Research (IMR), Malaysia, the oldest and leading medical research center in the country. A total of 84 questionnaires were distributed to the biomedical scientists and 54 filled-in questionnaires were returned with an overall response rate of 64.3 percent. The findings indicated that biomedical scientists use a variety of information sources to satisfy their information needs. Biomedical scientists who were solely involved in research work considered journal articles as the most preferred information source. On the other hand, researcher-cum-lecturers considered books as the most preferred information source in meeting their information needs. Both categories of scientists also considered interaction with colleagues as an important source for satisfying their information needs. The study also revealed that in spite of having access to modern and up-to-date digital information sources, most respondents still preferred using printed materials. Nonetheless, CD-ROM was the most utilized ITbased source. For the Internet-based information sources and applications, e-mail was the most popular while other applications were used infrequently.